2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6346699
|View full text |Cite
|
Sign up to set email alerts
|

Detection of baroreceptor activity in rat vagal nerve recording using a multi-channel cuff-electrode and real-time coherent averaging

Abstract: Electrical stimulation of afferent nerve fibers originating from pressure sensors can trigger the baroreflex to reduce blood pressure and might be an alternative to treat patients with hypertension. In this study, baroreceptor compound activity was detected using multi-channel cuff-electrode recordings on rat vagal nerve. In order to isolate the vagal nerve signals from external potentials (such as ECG- and EMG-coupling), a tripolar measuring technique was applied. To eliminate noise and neural signals corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
3
13
0
Order By: Relevance
“…Consequently, given the similarity between the cuff recordings and the intraneural recordings, the present intraneural‐derived BPnPs and RnPs could serve as markers for the BP and respiration, respectively. Consistent with our results, Plachta et al have recorded BP‐related signals from the LVN of rats using a polyimide cuff electrode . However, in contrast with our results, those BP‐related signals did not resemble the BP waves and the mentioned authors did not report whether or not those signals reflected in any way BP changes .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Consequently, given the similarity between the cuff recordings and the intraneural recordings, the present intraneural‐derived BPnPs and RnPs could serve as markers for the BP and respiration, respectively. Consistent with our results, Plachta et al have recorded BP‐related signals from the LVN of rats using a polyimide cuff electrode . However, in contrast with our results, those BP‐related signals did not resemble the BP waves and the mentioned authors did not report whether or not those signals reflected in any way BP changes .…”
Section: Discussionsupporting
confidence: 71%
“…Indeed, a recent study with cuff VNS for heart failure in humans showed inefficient recruitment of the targeted VN fibers , which indicates that selective activation of the human ABR fibers is improbable with such electrodes. Moreover, as the recording capabilities of the above‐mentioned selective cuff electrodes were tested in rats exclusively and only to locate the ABR fibers relative to the electrode contacts , it is unclear if such electrodes could be used to record ABR signals qualitatively suitable for the extraction of BP markers from a larger sized LVN.…”
Section: Introductionmentioning
confidence: 99%
“…The tripole contacts located near the baroreceptor fibers (ADN) were identified through coherent averaging [16]. These contacts were chosen for the stimulation procedure described below.…”
Section: Identification Of Baroreceptor Fibersmentioning
confidence: 99%
“…The surgeries and experiments occurred in a commonly grounded Faraday cage. The tripole contacts located near the baroreceptive fibers (ADN) were identified via coherent averaging, as previously described, by visual identification . Identification of ADN‐fibers is based on the assumption that the baroreceptive information has, due to its origin in pressure‐sensitive sensors in the aortic arch, a pulse‐synchronized, pulsatile character and can therefore be identified against the stochastically distributed background noise and activity.…”
Section: Methodsmentioning
confidence: 99%